PENGEMBANGAN MEDIA PEMBELAJARAN BUKU SAKU BERBASIS MIND MAPPING UNTUK MENINGKATKAN PRESTASI BELAJAR PPKn SISWA KELAS IV DI SD MUHAMMADIYAH KARANGWARU - Yuni Astriani; Rian Nurizka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research aims to: 1) determine the feasibility of Mind Mapping based pocket book learning media to improve learning achievement in Civics subjects on Pancasila class 4 SD Muhammadiyah Karangwaru; 2) find out the effectivenes of Mind Maping-based pocket book learning media to improve learning achievement in Civics subjects on Pancasila class IV SD Muhammadiyah Karangwaru. postest. The difference scale of increasing student achievement between the control class and the experimental clas tested with an independen sample t-test with a sig level 0.05. The results study are form of Mind Maping-based pocket book learning media. The results of expert assessment show the Mind Maping-based pocket book learning media is appropriate according to media experts and material experts with a good assessment category. The results show the Mind Maping-based pocket book learning media was effective in increasing student achievemen. Based on the results the operational field trials, it was obtained from the results of the independent sample T-test which showed that the acquisition of scores increased student achievement by less than 0.05 (0.000 < 0.05) or it mean that Ho reject and H1 accept, it can be conclud "There is a difference in improving the learning achievement of students who take part and do not take part in learning using Mind Mapping based pocket book learning media"